A Rare Case of Bullous Pemphigoid in an Infant - Pinto, Ana Marcos- (2021)
Bullous pemphigoid is an autoimmune blistering skin disease, rare in infancy, but increasingly reported. We describe a case of bullous pemphigoid in a 6-month-old infant with an excellent response to topical and oral corticosteroids. In this age group, the dermatosis assumes some particularities which must be recognized by clinicians in order to prevent unnecessary diagnostic workup or diagnostic delay and treat appropriately to avoid severe morbidity.